Factors Influencing Career Development in a Digitally Transforming Workplace - Rulia Sofa; Muhammad Irfan Nasution (Transpublika Publisher, 2026)
Digital transformation across various organizations has encouraged companies to understand the factors influencing employee career development in order to maintain competitiveness and improve the quality of human resources. This study aims to analyze the factors influencing career development in a digitally transforming workplace. The research employed a quantitative approach using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Empirical data were obtained from questionnaires completed by 50 permanent employees and selected using a purposive sampling technique. The findings indicate that educational attainment is the only variable that makes a significant contribution to employee career development (T-statistic = 4.317; p-value = 0.000). In contrast, work experience, Edupos, and Ihsanpos do not have a significant effect on career development because these variables are not yet fully aligned with digital competency requirements and the company’s promotion policies. The R-Square value of 0.653 indicates that the model explains 65.3% of the variation in career development, while the Q-Square value of 0.594 demonstrates good predictive ability; factors outside the model influence the remaining 34.7%. These findings confirm that formal education remains an important factor in supporting career advancement in the era of digital transformation. Therefore, organizations should strengthen human resource development policies focused on improving employees’ educational qualifications and continuously evaluate the effectiveness of training and performance appraisal systems to ensure better alignment with employee career development. This study is limited by its 50-employee sample, single regional setting, and 4 independent variables, which restrict generalizability and suggest that other factors may influence career development.